Conditional and Synthetic Type IV Pili-Dependent Motility Phenotypes in Myxococcus xanthus - Subedi, Kalpana; Wall, Daniel (Frontiers in Microbiology, 2022)
Myxobacteria exhibit a variety of complex social behaviors that all depend on coordinated movement of cells on solid surfaces. The cooperative nature of cell movements is known as social (S)-motility. This system is powered by cycles of type IV pili (Tfp) extension and retraction. Exopolysaccharide (EPS) also serves as a matrix to hold cells together. Here, we characterized a new S-motility gene in Myxococcus xanthus. This mutant is temperature-sensitive (Ts−) for S-motility; however, Tfp and EPS are made. A 1 bp deletion was mapped to the MXAN_4099 locus and the gene was named sglS. Null mutations in sglS exhibit a synthetic enhanced phenotype with a null sglT mutation, a previously characterized S-motility gene that exhibits a similar Ts− phenotype. Our results suggest that SglS and SglT contribute toward Tfp function at high temperatures in redundant pathways. However, at low temperatures only one pathway is necessary for wild-type S-motility, while in the double mutant, motility is nearly abolished at low temperatures. Interestingly, the few cells that do move do so with a high reversal frequency. We suggest SglS and SglT play conditional roles facilitating Tfp retraction and hence motility in M. xanthus.